Investigation of anthoicians availability in sunflower seed husks - Papchenko Victoriіa; Matveeva, Tatiana; Belinska, Anna; Rudniev, Vasyl; Zviahintseva, Oksana; Cherevichna, Nataliya (Technology audit and production reserves, 2017)
The comprehensive approach that provides a theoretical and experimental justification of a new feedstock for the production of anthocyanins is proposed. Such approach is needed in order to solve the problem of obtaining natural dyes. As sunflower is the main oilseed crop in Ukraine, hundreds of thousands tons of husks are obtained every year as secondary products (wastes) in fat and oil industry while processing its seeds. The must promising raw material for extraction of natural dyes is the sunflower husk as a cheap and affordable base. The presence of polyphenolic compounds in sunflower seed husks samples was determined by qualitative reactions. Quantitative determination of anthocyanins in sunflower seed husks samples was performed by spectrophotometric method. For this purpose anthocyanins were extracted from the previously defatted and crushed husks with an aqueous solution of HCl (1 % m/m). The average content of anthocyanins in terms of cyanidin-3.5-diglucoside reached up to 0.42 %.